Historians and their discipline the call of Southeast Asian history - Tarling, Nicholas (Monographs of the Malaysian Branch, Royal Asiatic Society, 2007)
Intended both for students and scholars, this book of personal essays is the first by a group of historians as researchers, writers and teachers speacializing in Southeast Asia.